2013
DOI: 10.1214/12-aoas624
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic effects on mortality revealed by panel analysis with nonlinear trends

Abstract: Many investigations have used panel methods to study the relationships between fluctuations in economic activity and mortality. A broad consensus has emerged on the overall procyclical nature of mortality: perhaps counter-intuitively, mortality typically rises above its trend during expansions. This consensus has been tarnished by inconsistent reports on the specific age groups and mortality causes involved. We show that these inconsistencies result, in part, from the trend specifications used in previous pane… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 56 publications
(150 reference statements)
7
34
0
1
Order By: Relevance
“…Other potential mechanisms linking macroeconomic swings with mortality oscillations are work environment factors, with slower rhythms of work and less overtime leading to less occupational stress and more time for sleep, physical activity, and social interaction, which is health promoting (Biddle & Hamermesh, ; Edwards, ; Eyer, , ; Sterling & Eyer, , ). More commuting and internal migration resulting from upturns in business activity might lead to an enhanced circulation of pathogens (Ionides et al, ). More frequent mild infections and higher pollution would increase the risk of acute cardiorespiratory events in persons carrying CVD or respiratory chronic disease (Ruhm, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other potential mechanisms linking macroeconomic swings with mortality oscillations are work environment factors, with slower rhythms of work and less overtime leading to less occupational stress and more time for sleep, physical activity, and social interaction, which is health promoting (Biddle & Hamermesh, ; Edwards, ; Eyer, , ; Sterling & Eyer, , ). More commuting and internal migration resulting from upturns in business activity might lead to an enhanced circulation of pathogens (Ionides et al, ). More frequent mild infections and higher pollution would increase the risk of acute cardiorespiratory events in persons carrying CVD or respiratory chronic disease (Ruhm, ).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research [14][15][16][17][18][19][39][40][41][42][43][44][45][46][47] has shown that in established market economies recessions are usually associated with improvements in population health. This is in spite that the associated increases in joblessness, business failures, and drops in tax returns often involve social service cuts, deterioration of health services, general social distress, and income reductions with financial problems for many.…”
Section: Discussionmentioning
confidence: 99%
“…Although this is an aggregate study, we examined this relationship at a granular geographic level (metropolitan and micropolitan areas) so that local changes in economic conditions identify the relationship. Previous U.S. research has mostly related state unemployment rates with state‐level measures of health (Ruhm , ; Ionides, Wang, and Tapia Granados ) or individual‐level data with state unemployment rates (Ruhm ; McInerney and Mellor ). Charles and DeCicca () used 1997–2001 individual data and metropolitan statistical area unemployment rates to examine the impact of unemployment on obesity and mental health measures.…”
Section: Summary Of Approachmentioning
confidence: 99%
“…These authors argued that this misspecification introduces a small amount of bias that does not significantly affect inference for total mortality, but the bias becomes more important for estimates of subgroup mortality. To implement this approach, we filtered unemployment using the Hodrick-Prescott filter (Hodrick and Prescott 1997) (HP filter), as suggested by Ionides, Wang, and Tapia Granados (2012), as well as other applied techniques suggested as alternatives. Ionides et al filtered all of the variables in the model.…”
Section: Analytic Approachmentioning
confidence: 99%